Utilizing Technology to Check the Assignments of Food Beverage Product Students - Anggayana, I Wayan Agus (Jurnal Manajemen Pelayanan Hotel, 2023)
This research utilizing technology to check the assignments simulates the use of Grammarly as one assessment tool for identifying errors in essays in writing English. The result analysis shows that Grammarly is used to assess the students’ grammatical and mechanical writing errors. From Grammarly report, it represents the quality of writing. Grammarly is an online proofreading service that checks for students’ grammar, spelling, and punctuation errors. Grammarly automatically verifies or detects the work typed based on various factors and reveals a variety of student writing errors, both in terms of grammatical and mechanical. This finding suggests that lecturers can use Grammarly, as automated software to implement corrective evaluation of Food Beverage Product Students' writing. This research is descriptive qualitative research. Researchers classify the issues in Grammarly: (a) Correctness (b) Clarity, (c) Engagement, (d) Delivery, the data taken only for the male of Food Beverage Product Students. Based on results and discussion, total Correctness 610, Clarity 12, Engagement 8, Delivery 1. For this research, male Food Beverage Product Students have more errors in Correctness, including Improved spelling, grammar, and punctuation, and one student writes in Indonesian. Keywords: Utilizing Technology, Food Beverage Product Students, Grammarly, Assignments